Case report: Anti-CNTN1 antibody-associated nodopathies disease with asymmetric onset - Li, Qian; Chen, Qing; Zhang, Ting; Xu, Ying; Kan, Yanmin; Zhang, Jing (Frontiers in Neurology, 2023)
Abstract Anti-contactin-1(CNTN1) IgG4 antibody-associated nodopathies is an autoimmune antibody-mediated peripheral neuropathy with a unique clinical presentation, pathophysiology, electrophysiology, and therapeutic response.The critical histopathological features are a dense lymphoplasmacytic infiltrate, a storiform pattern of fibrosis, and obliterative phlebitis. A 62-year-old male patient with subacute unilateral limb onset, progressive exacerbation, marked weakness of the extremities,cranial and autonomic nerve involvement. Neurophysiology showed slowed MCV (motor nerve conduction velocity), prolonged DML (distal motor delay), slowed SCV (sensory nerve conduction velocity), decreased SNAP (sensory nerve activity potential) amplitude, decreased amplitude of bilateral neuromotor conduction, abnormal SSR (cutaneous sympathetic response) in both lower extremities, axonal damage, prolonged F-wave latency, and discrete waves. In the initial phase, there was a response to intravenous immunoglobulin (IVIG), and corticosteroids and rituximab were also effective. After 1 year follow-up, the patient improved significantly. This article reports on a patient with nodular disease with anti-contactin-1(CNTN1) IgG4 antibodies and reviews the literature to improve clinicians' understanding of the disease.